The Morphological Analysis of Inflectional Plural Noun Suffixes Found in Catharsis Novel by Anastasia Aemelia - Laksmi , I G A Mas Chandra Paramita; Tustiawati , Ida Ayu Mela (Regalia Institute, 2023)
Novel is a long narrative story that describes the specific human experiences in their life as depicted by the portrait of the characters. A novel that is written by Anastasia Aemilia entitled Catharsis talks about the story of a troubled young woman with special gifts and heavy burdens. Observing inflectional suffix aims to enrich the language learners’ vocabulary especially noun in plural forms. This qualitative research focuses on the analysis of inflectional plural noun suffixes that are found in the novel entitled Catharsis. This study is also analyzed based on the theory that proposed by Katamba (1993) regarding to the research problem which about the types of inflectional plural noun suffix. The results that are found 681 data that contain inflectional suffixes. Those data are divided into 3 categories namely 646 data (95%) of plural noun suffix (-s), 28 data (4%) of plural noun suffix (-es), and 7 data (1%) of plural suffix (-ies).